Innate and Adaptive Immune Responses in HELLP Syndrome - Stojanovska, Violeta; Zenclussen, Ana Claudia (Frontiers in Immunology, 2020)
Innate and adaptive immune involvement in hemolysis, elevated liver enzymes, and low platelet (HELLP) syndrome is an understudied field, although it is of high clinical importance. This syndrome implies a risk of serious morbidity and mortality to both the mother and the fetus during pregnancy. It was proposed that HELLP syndrome occurs in a circulatory inflammatory milieu, that might, in turn, participate in a complex interplay between the secreted inflammatory immunomodulators and immune cell surface receptors. Meanwhile, reported immune cell attenuation during HELLP may consequently lead to prolonged immunoactivation and tissue damage. In this regard, learning more about the immune components of this syndrome should widen the understanding of the HELLP pathophysiology and eventually enable the development of novel immune-based therapeutics. This review aims to summarize and discuss the recent and previous findings of the innate and adaptive immune responses during HELLP in order to update the current knowledge of the immune involvement in HELLP pathogenesis.